(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
The experience of illness and its physical, emotional and social consequences present us with a challenge when viewed as limitations that affect negatively one’s dignity. Healing, on the other hand, can be perceived as restoration of one’s wholeness and therefore restoration of one’s dignity. The paper offers a biblical reflection on healing, showing that the divine vision for humanity is a disease-free existence, characterised by harmony and wellbeing. Thus, healing is an important aspect of God’s restoration. However, the value of human beings is not determined by their health status, but by their relationship with the Creator. And so it should be with one’s perception of human dignity.